Exploring biomarkers for noise-induced hearing loss through mitochondrial DNA methylation analysis - Wang, Dianpeng; Li, Caiping; Shi, Liuwei; Lin, Dafeng; Weng, Shaofan; Yang, Xiangli; Li, Peimao; Zhang, Zhimin; Zhang, Wen; Guo, Yan; Yang, Guangtao; Huang, Zhenlie; et al. (Frontiers in Pharmacology, 2025)
ObjectiveNoise-induced hearing loss (NIHL), resulting from occupational noise exposure, is a significant health concern with considerable economic and social implications. It is the most commonly reported occupational disease in developing countries. Noise causes cochlear cell damage by inducing mitochondrial oxidative stress elevating reactive oxygen species (ROS), ultimately leading to cell apoptosis. This study explores the impact of noise-induced oxidative stress on mitochondrial DNA methylation and aims to identify potential molecular biomarkers for NIHL.MethodsThis study included 40 cases of NIHL and 40 controls. Mitochondrial genome-wide methylation sequencing was performed using a targeted region approach with bisulfite multiplex PCR capture technology and high-depth next-generation sequencing (NGS).ResultsThe analysis revealed significant differences in methylation levels at 53 sites within mitochondrial genes, including 12S_rRNA, 16S_rRNA, tRNA-Ile, ND2, tRNA-Trp, CO1, CO2, ATP6, and CYB, with lower methylation levels observed in the case group compared to controls. In contrast, methylation levels at 31 sites, including 12S_rRNA, tRNA-Val, 16S_rRNA, CO1, CO3, ND3, tRNA-Arg, ND4, and ND5, were significantly higher in the case group. Receiver Operating Characteristic (ROC) curve analysis showed that the CYB gene had an area under the curve (AUC) of 0.807, with high sensitivity (0.90) and reasonable specificity (0.70).ConclusionThis study demonstrates a reduction in mitochondrial DNA methylation, particularly in the ATP6 and CYB genes, among individuals with NIHL. These findings suggest that mitochondrial DNA methylation, especially in the CYB gene, could serve as a potential biomarker for NIHL. However, given the complex interplay of various factors, including genetic, environmental, and lifestyle influences, further research is needed to fully understand the role of mitochondrial DNA methylation and oxidative stress in NIHL. Future studies should focus on identifying additional biomarkers and elucidating their mechanistic relationships, which could lead to more accurate diagnostic tools and therapeutic strategies.